2015
DOI: 10.1016/j.adolescence.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and psychosocial functioning in adolescence: An investigation among Indian students from Delhi

Abstract: While developmental studies predominantly investigated adolescents' mental illness and psychosocial maladjustment, the present research focused on positive mental health of Indian adolescents within the Mental Health Continuum model. Aims were to estimate their prevalence of mental health and to examine its associations with mental distress and psychosocial functioning, taking into account age and gender. A group of 539 students (age 13e18; 43.2% girls) in the National Capital Territory of Delhi completed Ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
48
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 49 publications
12
48
0
7
Order By: Relevance
“…Although prior studies using CFA have supported the tripartite structure of the MHC-SF in many cultures (e.g., Singh et al 2015), it seems that the close conceptual connections between the three factors of the MHC-SF would yield non-zero cross-loadings in the measurement model of the MHC-SF, which would be revealed by ESEM. Moreover, ESEM is likely to yield more accurate factor inter-correlations, which may turn out to be smaller than the ones produced by CFA.…”
Section: Esem Versus Cfamentioning
confidence: 93%
See 1 more Smart Citation
“…Although prior studies using CFA have supported the tripartite structure of the MHC-SF in many cultures (e.g., Singh et al 2015), it seems that the close conceptual connections between the three factors of the MHC-SF would yield non-zero cross-loadings in the measurement model of the MHC-SF, which would be revealed by ESEM. Moreover, ESEM is likely to yield more accurate factor inter-correlations, which may turn out to be smaller than the ones produced by CFA.…”
Section: Esem Versus Cfamentioning
confidence: 93%
“…The shortest measure to assess the tripartite model is the Mental Health Continuum-Short Form (MHC-SF), which has been widely used in prior research. These studies have provided evidence of adequate reliability and construct validity of the MHC-SF in a number of cultures, including South Africa, India, the Netherlands, Iran, Poland, and Italy (e.g., Joshanloo et al 2013;Karaś et al 2014;Keyes et al 2008;Lamers et al 2011;Singh et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…doi: 10.1111/jcap.12131 Adolescence is a crucial period in life marking the transition from childhood to adult age. Around 18% of the world's population is in this life stage (Murray & Newby, 2012) characterized by physical, cognitive, and socio-emotional changes that are often perceived as stressful and having potential negative consequences in terms of psychosocial adjustment (Singh, Bassi, Junnarkar, & Negri, 2015). In this period, an adolescent endeavors to gain a place in the social world by drawing up and realizing his/her personal plans and objectives.…”
Section: Informed Consentmentioning
confidence: 99%
“…Depression has been associated with adverse situations, deficits in social skills and psychosocial malfunction, such as low school performance, little involvement in recreational activities and with poor interpersonal relationships (Lewinsohn, Gotlib & Seeley, 1995;Nilsen, Karevold, RØysamb, Gustavson, & Mathiesen, 2013;Singh, Bassi, Junnarkar & Negri 2015). In a longitudinal study that took place during a period of about 10 years, in which patients' functioning was evaluated and variations in levels of symptomatology were considered, it was concluded that increasing levels of severity of depressive symptoms were significantly associated with an increase in restrictions in general functioning and in the work and interpersonal relationship domains (Judd, Akiskal, Zeller et al, 2000).…”
Section: Introductionmentioning
confidence: 99%